Comparison of high-flow nasal cannula and conventional oxygen therapy for high-risk patients during bronchoscopy examination: protocol for a randomized controlled trial - Hao Qin; Guo-Qiang Jing; Wei Tan; Jun Wang; Yi-Nan Yin; Rong-Zhang Chen; Wei Zhang; Jie Li (Trials, 2023)
Abstract Introduction High-flow nasal cannula (HFNC) has been proven to improve oxygenation and avoid intubation in hypoxemic patients. It has also been utilized during endoscopy examination to reduce the incidence of hypoxia. However, little is known about the effects of HFNC versus conventional oxygen therapy (COT) on oxygenation during bronchoscopy examination via nasal route; particularly, no study has compared the use of HFNC with that of COT at similar FIO2 for patients who have high-risk factors of desaturation during bronchoscopy examination. Methods and analysis This randomized controlled trial will be implemented in four academic centers in China. Patients who have high-risk factors including hypoxemia, hypercapnia, morbid obesity, and narrow airway will be enrolled to use HFNC or COT during bronchoscopy examination. In the HFNC group, the initial gas flow will be set at 50 L/min with a fraction of inspired oxygen (FIO2) at 0.45, if the patient tolerates, the flow can be increased to 60L/min at most, while in the COT group, oxygen flow will be set at 6 L/min via a conventional nasal cannula. After 5 min pre-oxygenation, the bronchoscope will be inserted via the nasal route. Vital signs, oxygenation (SpO2), and transcutaneous CO2 (PtCO2) will be continuously monitored. The primary outcome is the incidence of hypoxemia, defined as SpO2 < 90% for 10 s during bronchoscopy examination, and secondary outcomes include the need for treatment escalation and adverse events. Discussion Hypoxia is a common complication of bronchoscopy, our study attempted to demonstrate that HFNC may reduce the probability of hypoxia during bronchoscopy in high-risk patients. The results will be disseminated through peer-reviewed journals and national and international conferences. Trial registration http://www.chictr.org.cn/ : ChiCTR2100055038. Registered on 31 December 2021.